2014
DOI: 10.1111/iej.12371
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four gutta‐percha filling techniques in simulated C‐shaped canals

Abstract: The core-carrier technique was the most effective technique when assessed by gutta-percha area in this simulated C-shaped canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
0
31
1
4
Order By: Relevance
“…3,13 The efficiency of injectable, thermoplasticized gutta-percha in filling canal irregularities has already been recognized. 14 Placement of a master gutta-percha cone in the apical part of the root canal prior to injection has been suggested to prevent overfilling and apical extrusion. 15,16 The core-carrier technique, which uses heat-softened alpha phase gutta-percha encased in a plastic carrier, provides excellent adaptation of the material to the prepared canal walls and irregularities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13 The efficiency of injectable, thermoplasticized gutta-percha in filling canal irregularities has already been recognized. 14 Placement of a master gutta-percha cone in the apical part of the root canal prior to injection has been suggested to prevent overfilling and apical extrusion. 15,16 The core-carrier technique, which uses heat-softened alpha phase gutta-percha encased in a plastic carrier, provides excellent adaptation of the material to the prepared canal walls and irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is recommended that lateral-compaction be performed using ultrasonically energized spreaders producing frictional heat and plasticized gutta-percha to produce a homogeneous root filling. 14 Various obturation techniques present with various distinctive features; therefore, the null hypothesis of this study was to compare the push out bond strengths of MicroSeal and Obtura II (Obtura Corporation, Fenton, USA) obturation techniques using epoxy-based (AH Plus) and methacrylate-based (Epiphany) sealers.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that if ultrasonic vibrations were applied to the material for too long, large voids were produced which could be detected using radiography. Other research into the application of ultrasonic vibrations for dentistry revealed that for root canal treatment, a filling of greater density could be produced by using ultrasonics in the procedure, and again a lower number of voids were produced than using cold lateral compaction [17]. However, it was also stated that there remains a concern of the effect of heating on the substrate material which requires further investigation.…”
mentioning
confidence: 99%
“…A obturação do sistema de canais radiculares deve propiciar adequado selamento a fim de impedir a percolação de fluidos para o interior do canal e prevenir a reinfecção, dando condições para que ocorra o reparo da região apical e periapical (ELDENIZ; ORSTAVIK, 2009;GUIMARÃES et al, 2014;OZKOCAK;SONAT, 2015). Nesse sentido, a qualidade da obturação está relacionada com o material e com a técnica obturadora empregada (OZKOCAK; SONAT, 2015;SOO et al, 2015;VIAPIANA et al, 2015;HORIUCHI et al, 2016;SCHÄFER et al, 2016).…”
Section: Introductionunclassified
“…Estudos recentes têm demonstrado a presença de gaps e espaços vazios após obturação com utilização de diferentes técnicas de obturação dos canais radiculares (GUIMARÃES et al, 2014;CELIKTEN et al, 2015;SOO et al, 2015;VIAPIANA et al, 2015;SCHÄFER et al, 2016), diante disso, Guimarães et al (2014) propuseram a ativação ultrassônica do cimento endodôntico com objetivo de espalhar o cimento no interior do canal radicular e promover melhor adaptação interfacial entre o cimento obturador e as paredes do canal radicular.…”
Section: Introductionunclassified